Genome-wide identification of LHT gene family in Lonicera macranthoides Hand.-Mazz and their responses to abiotic stresses - Li, Zhaowu; Hu, Yue; Liang, Chunzhi; Chen, Lu; Hu, Yao; Wu, Xiaoqiu; Chen, Xia (Frontiers in Genetics, 2025)
Amino acid transporters (AATs) allow the transport of amino acids and play important roles in the various physiological processes and environmental responses of plants. The lysine and histidine transporter (LHT) subfamily is an important type of AAT. However, a genome-wide overview of the LHT gene family has not been conducted in L. macranthoides Hand.-mazz. In this study, 11 LHT genes were identified in the Lonicera macranthoides genome. To further understand the functions of LmLHT genes, the gene and protein characteristics, transmembrane helices, evolutionary relationships, chromosomal distribution, cis-acting elements of promoters, and expression patterns were systematically analyzed. According to the results, LmLHT genes were divided into two groups based on the phylogenetic analysis. Transmembrane helices of LmLHT proteins ranged from seven to 16. Gene structure and conserved motif analysis revealed that exon-intron structures and motifs were relatively conserved in the LmLHT family. LmLHT genes were distributed on six of the nine chromosomes and had the most collinear gene pairs with NtLHT genes. Additionally, phytohormones, low-temperature, drought-inducibility, defense and stress related cis-acting elements were enriched in the promoters of LmLHT genes. LmLHT genes showed distinct or preferential expression patterns in various tissues, signifying their potential roles in plant growth and development. We also found that some LmLHT genes were responsive to cold and drought stresses, indicating their roles in abiotic stress adaptation. Overall, our results provided comprehensive insight into the LmLHT gene family and will be useful for future functional analyses.